An open-label, controlled trial of the clinical effects of Laennec® in patients with nonalcoholic steatohepatitis or cirrhosis - M. Imawari; M. Nagase; I. Yu. Torshin; O. A. Gromova (Фармакоэкономика, 2023)
Objective: to evaluate the efficacy and safety of human placenta hydrolysate (HPH) Laennec® in the treatment of nonalcoholic fatty liver disease (NAFLD) in a clinical trial.Material and methods. The study involved hospitalized NAFLD patients (with non-alcoholic steatohepatitis, cirrhosis) (n=34, mean age 53±14 years). In the therapy group (n=17), patients received Laennec® HPH (4 ml intravenous drip infusion in a solution of 5% glucose 5 times a week for 2 weeks). In the control group (n=17), patients hospitalized in other departments of the clinic did not receive any therapy for NAFLD. The effectiveness of therapy was assessed after 2 and 3 weeks by subjective NAFLD symptoms (fatigue, anorexia, bloating, constipation, nausea, and pain in hypochondrium) and biochemical indicators of liver function: levels of blood serum aspartate aminotrans-ferase (AST), alanine notransferase (ALT), gamma-glutamyltransferase (GGT).Results. At the start of the study, there were no significant differences between the groups in the values of the studied indicators of liver function: blood levels of AST, ALT, GGT, etc. By the end of Week 1, a significant decrease in AST levels was registered in the group receiving Laennec® (–35 U/l; control: –8 U/l; p<0.001), ALT (–45 U/l; control: –10 U/l; p<0.001), and GGT (–23 U/l; control: –8 U/l; p=0.084; trend). At the end of the study (Week 3), the decrease in AST, ALT and GGT levels towards the normal range was even more pronounced for all three biomarkers: AST (–62 U/l; control: –23 U/l; p<0.001), ALT (–78 U/l; control: –20 U/l; p<0.001), GGT (–40 U/l; control: –15 U/l; p=0.005). Subjective NAFLD symptoms significantly improved after 3 weeks. No adverse effects were identified with the use of HPH. Conclusion. Laennec® is an effective and safe treatment for NAFLD.